PERUBAHAN STRUKTUR SOSIAL EKONOMI MASYARAKAT AKIBAT ALIH FUNGSI LAHAN DI DESA TRANSMIGRASI BATANG PANE II KECAMATAN HALONGONAN TIMUR KABUPATEN PADANG LAWAS UTARA - Rusdi Rusdi; Rizabuana Rizabuana; Ria Manurung; Badaruddin Badaruddin; Sismudjito Sismudjito (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The village community is synonymous with an agrarian society, this is marked by a livelihood as a farmer in fulfilling the economic needs of his family, so that the existence and ownership of land becomes very important. However, in the course of time, due to economic demands, it is not uncommon for people to convert land from paddy fields, namely subsistence crops to oil palm plantations. This condition occurs in the Transmigrant community of Batang Pane II Village. This condition attracts researchers to conduct studies by describing in depth the changes that occur in the conditions of socio-economic structure, status and roles, orientation of cultural values and stratification as a result of land conversion. The focus of this research is to find out what factors influence the occurrence of land conversion from paddy fields to oil palm plantations and what phenomena occur in structural, social and economic values due to land conversion to the lives of the second generation of people. In this study the research method used is descriptive method with a qualitative approach.